River-dominated pCO2 dynamics in the northern South China Sea during summer: A modeling study. (January 2021) - Zhao, Huade; Dai, Minhan; Gan, Jianping; Zhao, Xiaozheng; Lu, Zhongming; Liang, Linlin; Liu, Zhiqiang; Su, Jianzhong; Cao, Zhimian
Highlights: Our model well simulated the Pearl River Plume (PRP) and the spatiotemporal distribution of surface p CO2 . Controls of surface p CO2 differ substantially in near-, mid- and far-field PRP sub-regions. Primary production, plume current and CO2 buffer capacity jointly determine the PRP's role as an atmospheric CO2 sink. Abstract: River-dominated ocean margins (RiOMars), characterized by river plumes and abundant riverine nutrient inputs, are especially critical in determining the oceanic uptake of atmospheric CO2 . Using a well validated three-dimensional, coupled physical-biogeochemical model, we examined the dynamics of the carbonate system in the Pearl River Plume (PRP) during summer over a typical RiOMar in the northern South China Sea (NSCS). Sea surface p CO2 in the PRP was mainly influenced by a combination of physical processes, air-sea exchange, and biological activity. The interplay between these complex processes differed spatially and temporally depending on the evolution of the PRP. The latter was divided into three sub-regions: near-, mid- and far-field. In the near-field PRP, the evolution of surface p CO2 was primarily influenced by biological activity. Surface p CO2 decreased substantially at the initial stage as a result of phytoplankton blooms, and then increased due to the reduction in the phytoplankton and increase of zooplankton and detritus. In the mid-field, surface p CO2 was initially dominated by air-sea exchange. Subsequently, the rates of biological processes exceeded the rate of air-sea exchange, resulting in a strong drawdown of surface p CO2 or a strong sink for atmospheric CO2 . The far-field of the PRP acted as a weak CO2 sink, where surface p CO2 was dominated by air-sea exchange as biological processes were fairly weak. In addition, given that the air-sea CO2 equilibrium time is much longer than water residence time of the PRP, the biologically-mediated low p CO2 surface water was enabled to be transported far away from estuary. Taken together, the combined effect of enhanced primary production, strong plume current and strong seawater carbonate buffering capacity were responsible for maintaining low surface p CO2 levels in this subtropical RiOMar system.